AI and VUCA Are Here to Stay : What Should Business Schools Teach and How? - Shtaltovna, Yuliya (GILE Journal of Skills Development, 2026)
Drawing on recent conceptual and empirical work on metamodern education, Higher Education 4.0, and transdisciplinary AI-interoperable competencies, alongside European Commission and UNESCO policy frameworks, this food-for-thought article adopts an integrative approach that synthesises research evidence, policy analysis, and practice-based insights for business education leadership and management. As AI and persistent social crises and VUCA/BANI conditions have become structural features of contemporary organisational and educational life, business schools are now at the centre of intersecting technological, geopolitical, and societal disruptions. Against this backdrop, this article addresses a central question for higher education: what should business schools teach (and, more importantly, how) when uncertainty, crisis, and AI-mediated decision-making are no longer exceptional but systemic. The analysis demonstrates that traditional discipline-centred and tool-oriented pedagogies are, while still foundational, increasingly strained by the realities graduates face in AI-mediated and crisis-shaped environments and are no longer adequate on their own. Instead, effective business education requires a shift toward cultivating navigational capacities, including systems thinking, intercultural competence, ethical judgment, emotional resilience, and context-aware AI literacy. The article further argues that evolutionary pedagogies (such as case-based learning, simulations, project work under uncertainty, and reflective practice) are particularly effective in developing these capacities. It concludes that business schools can no longer define their mission primarily in terms of knowledge transmission or skills optimisation. Instead, they are called to assume a renewed social contract: preparing leaders capable of responsible action, ethical sensemaking, and sustained agency in AI-mediated, crisis-shaped environments, with significant implications for curriculum design, faculty roles, and higher education policy.